“We can’t share things with our teachers”: Narratives of mistrust and disconnect between South African female learners and their teachers - Duby, Zoe; Maruping, Kealeboga; Jonas, Kim; McClinton Appollis, Tracy; Vanleeuw, Lieve; Mathews, Catherine (Frontiers in Education, 2022)
The quality and nature of student-teacher relationships have implications outside of the academic domain. Support from teachers plays a significant protective role in the mental and emotional well-being of adolescents and young people, and can help to reduce or delay their engagement in risk behaviours, thereby decreasing negative sexual and reproductive health outcomes such as teenage pregnancy. Using the theory of teacher connectedness, an element of school connectedness, this research explores the narratives surrounding teacher-student relationships amongst South African adolescent girls and young women (AGYW) and teachers. Data were collected through in-depth interviews with 10 teachers, and 63 in-depth interviews and 24 focus group discussions with 237 AGYW aged 15-24 from five South African provinces characterised by high rates of HIV and teenage pregnancy amongst AGYW. Analysis of the data followed a thematic and collaborative approach, comprising coding, analytic memo-ing, and verification of emerging interpretations through discussion and participant feedback workshops. Findings related to perceptions of support and connectedness in teacher-student relationships centred around AGYW narratives of mistrust and a lack of support from teachers, and the consequential negative implications for academic performance and motivation to attend school, self-esteem and mental health. Teachers’ narratives centred around challenges providing support, feeling overwhelmed and incapable of fulfilling multiple roles. Findings provide valuable insight into student-teacher relationships in South Africa, their impact on educational attainment, and on the mental health and sexual and reproductive health of AGYW.